Analysis of lncRNA-miRNA-mRNA Expression in the Troxerutin-Mediated Prevention of Radiation-Induced Lung Injury in Mice - Zhang N; Song GY; Hu YJ; Wang X; Chao TZ; Wu YY; Xu P (Journal of Inflammation Research, 2023)
Nan Zhang,1,* Gui-yuan Song,2,3,* Yong-jian Hu,4 Xia Wang,4 Tian-zhu Chao,1 Yao-yao Wu,1 Ping Xu1 1School of Food and Biomedicine, Zaozhuang University, Zaozhuang, Shandong, 277160, People’s Republic of China; 2School of Public Health, Weifang Medical University, Weifang, Shandong, 261000, People’s Republic of China; 3Radiology Laboratory, Central Laboratory, Rizhao People’s Hospital, Rizhao, Shandong, 276800, People’s Republic of China; 4Henan Key Laboratory of Medical Tissue Regeneration, Xinxiang Medical University, Xinxiang, Henan, 453003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ping Xu, Tel +86 19863349848, Email 13273730271@163.comBackground: Radiation-induced lung injury (RILI) is a critical factor that leads to pulmonary fibrosis and other diseases. LncRNAs and miRNAs contribute to normal tissue damage caused by ionizing radiation. Troxerutin offers protection against radiation; however, its underlying mechanism remains largely undetermined.Methods: We established a model of RILI in mice pretreated with troxerutin. The lung tissue was extracted for RNA sequencing, and an RNA library was constructed. Next, we estimated the target miRNAs of differentially expressed (DE) lncRNAs, and the target mRNAs of DE miRNAs. Then, functional annotations of these target mRNAs were performed using GO and KEGG.Results: Compared to the control group, 150 lncRNA, 43 miRNA, and 184 mRNA were significantly up-regulated, whereas, 189 lncRNA, 15 miRNA, and 146 mRNA were markedly down-regulated following troxerutin pretreatment. Our results revealed that the Wnt, cAMP, and tumor-related signaling pathways played an essential role in RILI prevention via troxerutin using lncRNA-miRNA-mRNA network.Conclusion: These evidences revealed that the abnormal regulation of RNA potentially leads to pulmonary fibrosis. Therefore, targeting lncRNA and miRNA, along with a closer examination of competitive endogenous RNA (ceRNA) networks are of great significance to the identification of troxerutin targets that can protect against RILI.Keywords: troxerutin, radiation-induced lung injury, ceRNA, lncRNA-miRNA-mRNA network, AKT, wnt signal pathway